Identifikasi Telur Soil Transmitted Helminths (STH) Dan Hubungannya Dengan PHBS Pada Anak-Anak Yang Tinggal Disekitar Daerah Tempat Pembuangan Akhir Sampah Sumompo - Indra Elisabet Lalangpuling; Firah Mutiara Nikiulu; Sabrina Prisscilya Magdalena Pinontoan (POLTEKKES KEMENKES MANADO, 2021)
Infection Soil Transmitted Helminths (STH) is an infection that is caused by a nematode gut that the transmission requires medium soil. Factors that support the transmission of soil-transmitted helminthes worm eggs in Indonesia are hygiene and poor living habits. This study aims to identify the presence or absence of intestinal parasitic infection which is caused by the egg Soil Transmitted Helminths (STH) and to determine the relationship existence of Soil Transmitted Helminths (STH) with PHBS in children who live around the area Points Disposal Final (TPA) Waste Sumompo. Type of research this is an analytic that is performed on 30 samples were determined by purposive sampling. The collection of data obtained from the results of filling the questionnaire and examination of samples in laboratory. Examination of the samples is done using the method of native (eosin 2%) and the concentration of flotation. Data analysis used the chi square test to see the relationship between helminth infections and PHBS, with a significance value of α= 0.05. Results of the study show the presence of infection Trichuris trichiura on children who live in the surrounding area Points Disposal Final Sumompo as many as three (10%). Results Analysis chi square to see the relationship of infection of worms with Behavioral Living Clean and Healthy (PHBS) showed no relationship that significant between infection of worms with the habit of playing on the ground without the use of footwear, custom cutting the nails, washing hands before eating, wash hands after Discard Air Besar, the habit of biting nails, and the availability of latrines at home.